EKSTRAKSI OTOMATIS INFORMASI DEM DARI CITRA STEREO PRISM-ALOS - Trisakti, Bambang (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2007)
ALOS satellite was launched on January 24th 2006 and is equipped by PRISM sensor which has a mission to produce stereoscopic image. PRISM is a panchromatic radiometer with 2.5 spatial resolution, and it has 3 telescopes for recording the image from nadir, forward and backward view is known as stereoscopic image which is usefull to generate earth surface height or DEM (Digital Elevation Model). Automatic DEM extraction was done by area based matching technique using PRISM DEM software. This technique correlates area/pixel in master image with same are/pixel in target image based based on grey value similarity of pixel. Relief displacement (parallax) of each area/pixel was extracted from the correlation process, and then it was used to generate earth surface height or DEM. The generated DEM was compared with reference data (SRTM X and C band) to analyze the level of DEM accuracy. The result shows that DEM from automatic extraction needs geoids correction (Eart surface relief correction). After doing the correction, the DEM has similar distribution height but smoother DEM pattern than referenced DEM. Finally, RMSE of PRISMDEM are around 16 m relative to the referenced DEM.